2012
DOI: 10.1021/pr300630k
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Comprehensive Characterization of a Human Cancer Cell Phosphoproteome

Abstract: Mass spectrometry (MS)-based phosphoproteomics has achieved extraordinary success in qualitative and quantitative analysis of cellular protein phosphorylation. Considering that an estimated level of phosphorylation in a cell is placed at well above 100,000 sites, there is still much room for improvement. Here, we attempt to extend the depth of phosphoproteome coverage while maintaining realistic aspirations in terms of available material, robustness, and instrument running time. We developed three strategies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
287
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 382 publications
(315 citation statements)
references
References 65 publications
(118 reference statements)
24
287
2
2
Order By: Relevance
“…Multiple large-scale proteomic analyses have indicated that Cdc7 is phosphorylated at Ser16, Ser302, and Thr503 in prometaphase, [26][27][28] which is consistent with our prediction (Fig 1E.). To further confirm it, we determined the extent of hyper-phosphorylation in vivo by two-dimensional PAGE with mycFLAGtagged Cdc7 WT and Cdc7 £5A expressed in HEK293T cells.…”
Section: Cdc7 Is Phosphorylated During Prometaphase In a Cdk1-dependesupporting
confidence: 92%
See 1 more Smart Citation
“…Multiple large-scale proteomic analyses have indicated that Cdc7 is phosphorylated at Ser16, Ser302, and Thr503 in prometaphase, [26][27][28] which is consistent with our prediction (Fig 1E.). To further confirm it, we determined the extent of hyper-phosphorylation in vivo by two-dimensional PAGE with mycFLAGtagged Cdc7 WT and Cdc7 £5A expressed in HEK293T cells.…”
Section: Cdc7 Is Phosphorylated During Prometaphase In a Cdk1-dependesupporting
confidence: 92%
“…This may be due to Cdc7 autophosphorylation 14 or phosphorylation by other kinases such as polo-like kinase (Plk), as large scale proteomics studies indicated that Plk phosphorylates Cdc7 at Serine 27 and 277 in prometaphase. 26,28,[30][31][32][33] In any event, our data demonstrate that Cdc7 is phosphorylated at multiple sites in a mitotic Cdkdependent manner around prometaphase.…”
Section: Cdc7 Is Phosphorylated During Prometaphase In a Cdk1-dependementioning
confidence: 61%
“…All peptides will bind to a cation exchanger at low pH condition, and bound peptides are predominantly separated by a stepwise elution with increasing ionic strength and/or increasing pH value. 28 Through the above process, the peptides obtained from complex biological sample are divided to 6~12 fractions. Phosphoprotein (or phosphpeptides) bound to SCX matrix are eluted in the early fractions, and peptides except for phosphorylated counterparts are eluted gradually on high salt or pH conditions.…”
Section: Strong Cation Exchange (Scx )mentioning
confidence: 99%
“…HILIC has been reported frequently in recent years in phosphoproteomic studies, because highly hydrophilic solutes as phosphorylated ones in comparison with common peptides are retained on the column for the longest time. [28][29][30] In HILIC, hydrophilic components acquired from biological specimens are typically bound onto HILIC column matrix when used with below 10 % aqueous. To isolate the phosphopeptides from ordinary ones, all peptides are fractionated by predominantly increasing the aqueous mobile phase up to 40% (Figure 2-B).…”
Section: Hydrophilic Interaction Chromatography (Hilic)mentioning
confidence: 99%
See 1 more Smart Citation